2000
DOI: 10.1088/0953-4075/33/16/103
|View full text |Cite
|
Sign up to set email alerts
|

Accurate probing of the repulsive X2Σ and B2Σ potentials of NaNe and NaAr by differential optical collision experiments

Abstract: The oscillations observed in the differential cross section of the optical collisions Na(3s) + M + hν → Na(3p) + M with M = Ne, Ar are compared with theoretical results from coupled-channels calculations using the best available potentials. Generally, a very good agreement is found. We conclude that repulsive interatomic potentials can be probed by this method with an accuracy of the order of only a few cm −1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…For Na·Kr, a modified HFD function was used to describe the X state, while the Morse function was utilized for the A state. The B state used in the simulations of the absorption and emission spectra of the Na·Ar system were those calculated by Kerner and Meyer. , These theoretical results were in good agreement with experimental results reported by Grosser, Hoffmann, and Rebentrost for the repulsive B potential. Rebentrost and co-workers determined the Na·Kr, B 2 Σ 1/2 state potential from collision-induced absorption data.…”
Section: Theoretical Methodssupporting
confidence: 83%
“…For Na·Kr, a modified HFD function was used to describe the X state, while the Morse function was utilized for the A state. The B state used in the simulations of the absorption and emission spectra of the Na·Ar system were those calculated by Kerner and Meyer. , These theoretical results were in good agreement with experimental results reported by Grosser, Hoffmann, and Rebentrost for the repulsive B potential. Rebentrost and co-workers determined the Na·Kr, B 2 Σ 1/2 state potential from collision-induced absorption data.…”
Section: Theoretical Methodssupporting
confidence: 83%
“…In the following, we will focus our attention on alkali-argon species. 16 -18,23,24 More recently, Kerner and Meyer have developed calculations using core polarization pseudopotentials which yield high quality potentials and were cited in several recent experimental works concerned with accurate determination of differential cross sections in Na-rare gas optical collisions 25 or high resolution spectroscopy studies. Very recently, the ground state of metal-rare gas dimers was also studied using coupled-cluster CCSD͑T͒ calculations.…”
Section: One-electron Pseudopotential Calculations Of Excited States mentioning
confidence: 99%
“…We stress that this result is interesting in the sense that the existence and uniqueness of the solution of the inverse problem is completely guaranteed in this case. Indeed, on one hand, it can be shown that the integral in (14) always converges; on the other hand, the uniqueness of this type of Abel transformation is well known. The final analytic expression for reconstructing the potential v 2 (r) follows from Eqs.…”
Section: Determining the Potential V 2 (R): A Standard Approachmentioning
confidence: 98%
“…The source of accurate information about such potentials is differential optical collisions [14] and observations leading to the measurement of the refraction index of a given atomic wave transmitted through a medium of rare gas atoms [15]. In the proposed example, we focus on the elastic scattering of the Na-He system.…”
Section: Improvement With Respect To the Standard Casementioning
confidence: 99%